북한이탈주민 전문상담사의 심리적 소진의 원인 탐색 - 노인숙; In Suk Rho; 조선희; Sun Hee Cho (정신간호학회지, 2012)
This study was done to identify the causes of burnout among South Korean counselors for North Korean refugees. Methods: Data were collected using open-ended questions in a survey from 85 South Korean counselors for North Korean refugees, and a content analysis of the textual data from the questions was conducted. Results: A total of 192 statements were selected from the data and those were categorized into 3 domains, 8 categories, and 24 sub-categories. Institutional, client, and social recognition domains emerged. Findings indicate that the causes of burnout were derived from the following categories: 1) the categories for the Institutional domain were physical environment, work conflict, and work overload, 2) for the client domain, lack of cooperation, selfish attitude, and limits to interventions, and 3) for the social recognition domain, lack of rewards and identity confusion. Conclusion: The results indicate that community mental health professionals need to understand these causes of burnout among the counselors working with North Korean refugees. It is also necessary to do further research to develop strategies to prevent burnout and potential mental health problems for these counselors.